(untitled) (Third Sector Social Economic Review, 2021)
While there has been a growing literature on “dark personality traits” (i.e., socially avoidant traits), there has been a lack of integration with the evolving research literature on positive traits and satisfying and growth-oriented outcomes in life. In order to help the field move towards greater integration, we would like to adapt the Light Triad which measured by the 12-item Light Triad Scale (LTS) to Turkish. The LTS is the first measure of a loving and beneficial orientation towards others (“everyday saints”), which consists of three aspects: Kantianism-Kantian (treating people as an end), Humanism-Humanian (valuing the dignity and worth of each individual) and Faith in Humanity (people’s dignity believing in its basic goodness) (Kaufman et al., 2019). The adaptation of the Light Triad Scale into Turkish will contribute positively to more principled and data-based approaches to discover the beneficial aspects of human nature. With the study, a scale that will help us to reveal the positive aspects of personality will be given to the literature and the opportunity to examine different relationships related to these personality traits will be provided.